Comprehensive ophthalmology - Khurana, A. K.; Khurana, Aruj K.; Khurana, Bhawna (Jaypee, The Health Sciences Publisher, 2015)
The sixth edition has been thoroughly revised, updated and reorganized into a new layout with six sections: • Section I: Anatomy and Physiology of Eye includes two chapters. First chapter is devoted to essential aspects of Anatomy and Development of the Eye, and second chapter covers Physiological aspects of various ocular structures including Physiology of Vision in a concise manner. • Section II: Optics and Refraction-Out of two chapters of this section one is devoted to Elementary and Physiological Optics and the other describes Errors of Refraction and Accommodation in depth. • Section III: Diseases of Eye- This section covers important diseases of various structure components of the eyeball, ocular adnexa and visual pathway in fourteen chapters. • Section IV: Ocular Therapeutics- This section comprises two chapters one each on Ocular Pharmacology, and Lasers and Cryotherapy in Ophthalmology. • Section V: Systemic and Community Ophthalmology-Includes two chapters one on each topic. • Section VI: Practical Ophthalmology- This section includes chapters on Clinical Methods in Ophthalmology and different other aspects essential to the practical examinations such as Ophthalmic Cases, Darkroom Procedures, and Ophthalmic Instruments. • Review of Ophthalmology- This companion to the textbook provides an in depth revision of the subject at a glance and an opportunity for self-assessment, and thus makes it the book of choice for preparing for various postgraduate entrance examinations.